Crystal Reports XI : official guide - FitzGerald, Neil, MBA (Sams, 2006)
The authorized guide to the latest edition of the #1 business intelligence software product - Crystal Reports. More than 16 million licenses of Crystal Reports have been shipped to date. This book is a reference designed to provide hands-on guidance for the latest release of the product suite. The latest version of Crystal Reports and the Business Objects enterprise reporting suite delivers vast product enhancements and a tighter integration that will drive upgrades from licensees. Brand new features (e.g. Dynamic and Cascading Parameter Generation) will also appeal to new audiences. Over 1 million new Business Intelligence licensees will be migrating to the Crystal Enterprise Reporting platform, as this is the first release of the software with the existing Business Objects (BO) products being integrated into the Crystal infrastructure. As Business Objects insiders, the authors bring unique and valuable real-world perspectives on implementations and uses of the Crystal Reports product. The book also includes content, tutorials and samples for reporting within the Microsoft Visual Studio.NET and J2EE development environments and also on top of the SAP Business Information Warehouse (BW) and the Peoplesoft platform. Advanced content on report distribution and integration into the secured managed reporting solution known as Business Objects Enterprise XI, is also now included in this definitive user guide with coverage on the new Web Services SDK.